English homework : is it a burden or help for students - Jecquline, Gelau. (Universiti Malaysia Sarawak, UNIMAS, 2008)
This study investigated the English homework practices whether it is a burden or help to secondary school students in SMK Agama, Sibu. 259 participants form upper and lower form levels took part in the survey and responded to the questionnaires distributed. Results showed that students were given 3- 2 times English homework and the amount was just right for them. Majority of respondents agreed that they often given textbook and workbook exercises completion tasks for their homework. Students valued the importance of homework and show positive reactions toward homework completion.